Analisis Kemampuan Penalaran Matematis Menggunakan Model PBL Ditinjau Dari Kecerdasan Intrapersonal - Waluyo, Sujoko (Lembaga Penelitian dan Pengabdian Masyarakat, 2023)
The purpose of this study is to determine the state of mathematical reasoning ability using the PBL model in terms of intrapersonal intelligence. The instruments used were reasoning ability tests, intrapersonal intelligence questionnaires and interview guidelines. Data analysis uses the Mile and Huberman models. The subjects in this study were students of SMP N 1 Tamiang Hulu. Students who were given problem-based learning treatment totaled 30 people. High ability students were 8 students or (26.67%), medium ability students were 18 students or (60%) and low ability students were 4 people or (13.34%). The conclusion of mathematical reasoning abilities using a problem-based learning model, 7 students or (23.33) high ability students, 13 students or (43.33%) moderate ability students and 10 low ability students. or (33.33%)